Visual Enjoyment Factor in Playability: Case Study of Real Time Strategy Games - Jaibi, Sabian (2021)
Each game has its own unique feature, which attracts players by continually playing the game on a daily basis. The game appeal also concerns interface attributes, game mechanics, and interfaces designed to stimulate excitement in playing the game. However, there is little discussion about the perceived visual enjoyment factor in artistic playability, especially among youth based on the Real-Time Strategy (RTS) game to support this statement. This research was carried out using the System Usability Scale (SUS) (Brooke, 1986), interviews and questionnaires. The use of SUS is trusted by its reliability and has become an industry standard with numerous references. Based on the findings, the results show that the players are pleased with the mechanics of the game; however, the players are relatively enthusiastic about the competitive challenge of finishing the game and achieving their goal. The visual is also not the driving factor for the player to keep playing the game, but the desire to complete the competitive challenge to feel satisfied until the game is over. The game enjoyment factor is more critical than usability, because it defines playability in the DOTA 2 game. Other than that, DOTA 2 is more extensive and significantly dependent on CTPM (Critical Thoughts Per-Minutes) and communication within the team, because critical thinking is very much needed to perceive enjoyment, but the depth, breadth and speed needed to apply the game to make a difference. If the players play their role while playing the game, they will also develop a particular style of leadership that will lead the team to victory and reduce the emotions while playing the game.